An assessment of the lipopolysaccharide toxicity of rough and smooth escherichia coli strains cultivated in the presence of zygosaccharomyces bailli - Mogotsi, Lerato Bonolo (Bloemfontein : Central University of Technology, Free State, 2011)
In nature microorganisms do not exist alone, but in association with one another. These kinds of associations can also be found in food industries, where cells of the same or different species can attach to pipes (biofilm formation) and a variety of surfaces in food processing environments and in food product such as yoghurt which can contain both yeast and bacteria originating from the starter culture as well as fruit. To control food spoilage organisms and food-borne pathogens preventative measures such as good manufacturing processes, the use of sanitizers and preservatives as well as hazard analysis critical control points (HACCP) are crucial in food industries. Sanitation of the working surface, floors, pipes, containers and equipment is a stepwise application of a detergent, acid or alkali rinse, a disinfectant treatment followed by final rinsing. If rinsing of the sanitizer is not done properly it may end up in the product in sub-lethal doses. In this study the influence of Liquid Hypochlorite (LH) and Liquid Iodophore (LI) sanitizers on organism growth and toxicity was evaluated. The organisms investigated included Escherichia coli 0113, Escherichia coli 026 and Zygosaccharomyces bailii Y-1535 in yeast malt broth, which was supplemented with LH and LI at sub-lethal concentrations 0.05% LH, 0.2% LH and 0.075% LI. Subsequently, bacterial and yeast growth responses as pure cultures and in combination (E. coli + Z. bailii) were measured as colony forming units and optical density values. Incorporation of the sanitizers in the growth media resulted in different levels of growth inhibition. Z. bailii proved more robust and the growth rate was not influence significantly by the addition of sanitizers or communal growth with either E. coli strains. The growth rate of both E. coli strains decreased where grown in combination with Z. bailii as well as in the presence of sanitizers, with the most influence exerted by LH. Changes in endotoxicity following the growth of the test samples (stressed cells) and the control (unstressed) were measured by the limulus amoebocyte lysate (LAL) and porcine IL-6 ELISA methods. Where E. coli strains were cultured together with Z. bailii the toxicity of tire mixture showed a decrease over time when measured with the limulus amoebocyte assay method. Interestingly the communal growth of the E. coli strains and Z bailii produced different toxicity profiles when the IL-6 porcine method was used, hi both cases, where E. coli strains were cultured together with Z. bailii the toxicity of the mixture showed an increase over tune when measured by this assay. Other than a similar toxicity profile for E. coli 0113 grown in pure culture, the comparison between results obtained using the LAL or porcine IL-6 methods yielded no correlation in determined toxicity. It was established that LH and LI sanitizers as well as communal growth had an influence in the toxicity of LPS/EPS and the method used to determine such toxicity should be carefully considered.
Thesis (M. Tech. Environmental health) -- Central University of technology, Free State, 2011
Keywords: Central University of Technology, Free State - Dissertations; Food contamination; Food industry and trade - Quality control; Disinfection and disinfectants; Microbial toxins; Yeast fungi; Microbial contamination; Dissertations, academic - South Africa - Bloemfontein